ATTRIBUTES INFLUENCING CUSTOMER PATRONAGE: EVIDENCE FROM A DEPOSIT MONEY BANK IN NIGERIA (Journal of the Management Sciences, 2025)
This study investigates the determinants of customer patronage in Nigeria’s banking sector, using Sterling Bank Nigeria Plc as a focal case. Six key factors—ambience, quality of service/service efficiency, digital infrastructure, emotional attachment/brand familiarity, perceived trustworthiness/social–regional affiliations, and bank performance—were examined using regression analysis, chi-square tests, and factor analysis on data obtained from 120 respondents. Findings indicate that all six variables exert a positive and statistically significant influence on customer patronage, with bank performance, service quality, and digital infrastructure emerging as the strongest predictors. Factor analysis further shows that these three constructs collectively account for more than 66% of the variation in patronage levels. The study concludes that customer patronage in the banking industry is both performance-driven and perception-sensitive, shaped by financial robustness, service efficiency, digital capability, and relational trust. It recommends that banks deepen investments in digital modernization, enhance service delivery standards, strengthen corporate performance, and cultivate social trust to maintain competitive advantage in the evolving post-digital banking landscape.
Keywords: Bank performance; service quality; digital infrastructure; trust, emotional attachment; customer patronage